Percentage And Intensity Of Stick Cancer (Phythotora Palmivora. Butler) On Cocoa Plants (Theobroma Cacao) And Its Influence On Dry Cocoa Bean Production (Kg) - Defitri, Yuza; Marpaung, Ridawati; Reza, Ahmad (Information Technology and Science (ITScience), 2024)
This study aims to determine the intensity and percentage of P. palmivora stem canker disease and identify the types of disease that occur on cocoa plant stems (Theobroma cacao) as well as the influence of the intensity and incidence of stem canker on stem canker disease. production of cocoa beans (T. cacao). The method used in this research is the observation method, the procedure for determining the research location was carried out by means of purposive sampling. The results of the research showed that the sample plants that were attacked by stem cancer showed symptoms of attack such as brown, purplish red stems, no holes, wet skin texture and black spots like rot. The highest percentage of stem cancer attacks was on plantation 3 at 37.78% and the lowest percentage of stem cancer attacks was on plantation 1 at 11.11%. The highest intensity of stem cancer attacks was on plantation 3 at 17.33% and the lowest intensity of stem cancer attacks was on plantation 1 (maintained) with an attack percentage of 6.39%. The results of observations on cocoa plant stem samples found a type of disease belonging to the Phytophthora palmivora fungus group at research locations 1, 2 and 3.